Structure-Function analysis of a novel DNA-binding domain of the histone acetyltransferase MOZ/KAT6A - Schoenfeld, Jonas (2019)
In this study, we focussed on the poorly characterised NEMM domain comprised within the N-terminal 200 amino acids of the Monocytic Leukemia Zinc Finger Protein (MOZ/KAT6A). MOZ is an important developmental regulator and involved in several diseases such as neurodevelopmental disorders and cancers. The NEMM domain of MOZ was recently found to be essential for induction of acute myeloid leukemia (AML) by the pathological fusion protein MOZ-TIF2. Structural predictions suggest that this region forms a potential tandem winged-helix domain (WHD) as found in a subfamily of DNA-binding proteins. Consistent with this, EMSA experiments indicated that the NEMM formed complexes with random dsDNA fragments in vitro. Mapping analysis showed that the first predicted winged-helix domain (pWHD1) preferentially binds dsDNA sequences containing CpG motifs, whereas the preference for pWHD2 was not defined. However, the data suggest that the tandem WHDs may form a composite DNA interaction-surface. Preliminary mutational analysis defined a lysine-rich stretch as necessary for DNA-recognition by pWHD1. Large-scale purification of MOZ pWHD1 free from contaminating DNA was also optimised, generating high yields of homogenous protein for protein crystallisation trials. In addition, mutations that disable the DNA-binding activity of MOZ or the function of the DPF and MYST domains were generated by site-directed mutagenesis in YFP-tagged full length MOZ. These were assessed in rescue experiments using CRISPR-Cas9 edited HEK293 cells depleted for MOZ expression. Even though preliminary data suggests functional impairment of mutated MOZ, the method was limited by uneven expression levels of mutant and WT constructs. Further experiments are required to determine if there is instability of mutant proteins, or if expression can be normalised to WT MOZ in future studies. In summary, this study has uncovered a potential tandem winged helix domain at the N-terminus of the MOZ acetyltransferase that has DNA-binding activity and a preference for CpG motifs. This constitutes a novel function of MOZ which has not been observed previously. Optimisation of protein purification and preliminary mutagenesis data will aid the full characterisation of this domain in future studies.